A Statistical analysis on Ultra Dong Shin Corporation - Abalos, Maria Lourdes; Aspera, Romeo; Entico, Ma. Cecilia; Rodriguez, Sharmaine (Diliman, Quezon City College of Engineering, 2002)
A statistical analyis was conducted on Ultra Dong Shin Corporation, a manufacturing plant concerned with the production of pre-insulated panels. The company was the first to introduce the use of PIR (polyisocyanurate) foam on ordinary panels to further enhance its capability to provide adequate shelter and improve the versatility through wider product application. Ultra Panels were primarily designed to service facilities requiring controlled temperature. Ultra Dong Shin Corporation is a partnership between DN Steel Group of Companies and South Korea's Ultra Dong Shin Heavy Industries Co., Ltd. The factory is located at San Felix, Sto. Tomas, Batangas. The project study is concerned with the identification of the possible causes of rejection and the application of the techniques of statistical analysis to prove the validity of the hypothesis. Several factors of rejection were identified and the factor that contributed the most number of cases was focused on and analyzed. Records of the company from January to March of 2000 showed that variation from the specified thickness of the panels constitutes 60% of the plant's rejection rate. The study concentrated on the production of UPW-200 Wall Panel System not only due to its popularity but because 65% of the whole production volume is attributed to this product. The pouring of the chemicals (components of PIR foam) is the most critical part of the production process and the stage responsible on the resulting thickness of the panels. Four factors need to be checked during this stage namely, pressure (inside the conveyor), temperature (inside the conveyor), cooking time (measured through line speed) and the density of the chemicals prior to pouring. The project proponents were provided only with data on temperature and line speed, so the study focused on the possible contributions of these two factors on the thicknes of the panels. Test for normally was first conducted in order to determine if the data gathered follows a specified distribution. Both the temperature and line speed were proven to follow a normal distribution. With this result, a test for analysis of variance (ANOVA) was performed and the outcome proved that indeed, temperature and line speed have great significance on the final thickness of the wall panels. The group then performed the 2 Factorial Experiment to further investigate the effects of the line speed and the cooking time on the thickness of the foam produced. Results showed that increasing the line speed would decrease the thickness of the foam while increasing the cooking temperature would increase its thickness. Also, increasing the interaction of these two factors would tend to decrease the thickness of the foam. The magnitude of the these effects were also analyzed and the group found out that the line speed has twice the effect on thickness compared to the effect of temperature and the interaction of the two on the thickness of the wall panel system. A test for Analysis of Variance (ANOVA) was then conducted and the outcome proved that indeed, temperature and line speed has great significance on the final thickness of the panels. To further standardize the thickness, the line speed must be kept at the high level and the temperature at the low level. The ANOVA for the Test on the Significance of Regression proved that thickness is linearly related to the model in either factor of line speed or temperature or their interaction. To further validate the results, a measure of Adequacy of the Regression Model was conducted. The Coefficient of Multiple Determination, R was computed to be 75.48%. That is, 75.48% of the variability in thickness could be explained when the regressor variables, line speed and temperature are used. Lastly, the test for the Existence of Multicollinearly was performed and proved that multicollinearity is somewhat a minor problem. The estimates of the regression coefficients are therefore precise. The results of these tests validated our hypothesis that line speed and cooking time have significant effects on the thickness of the PIR foam of the UPW-200 Wall Panel System. It is therefore recommended that these two factors be kept near their specifications in order to minimize the deviation from the specified thickness. Furthermore, proper machine settings which will reduce the variations in the thickness of the PIR panels and the proper maintenance of these machines should be determined and implemented.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 28 : Statistical Analysis for Industrial Engineering
Keywords: Statistics